Prospective Assessment of Early Proton Therapy-Induced Optic Neuropathy in Patients With Intracranial, Orbital or Sinonasal Tumors: Impact of A Standardized Ophthalmological Follow Up - Lecornu, Marie; Lesueur, Paul; Salleron, Julia; Balosso, Jacques; Stefan, Dinu; Kao, William; Plouhinec, Tiphaine; Vela, Anthony; Dutheil, Pauline; Bouter, Jordan; Marty, Pierre-Alban; Thariat, Juliette; et al. (Frontiers in Oncology, 2021)
Purpose: proton therapy (PT) can be a good option to achieve tumor control while reducing the probability of radiation induced toxicities compared to X-ray-based radiotherapy. However, there are still uncertainties about the effects of PT on the organs in direct contact with the irradiated volume. The aim of this prospective series was to report 6-month follow-up of clinical and functional optic neuropathy rates of patients treated by proton therapy using a standardized comprehensive optic examination. Methods and Materials: Standardized ophthalmological examinations were performed to analyze subclinical anomalies in a systematic way before treatment and 6 months after the end of proton therapy with: Automatic visual field, Visual evoked potential (VEP) and optic coherence of tomography (OCT). Results: From October 2018 to July 2020 we analyzed 81 eyes. No significant differences were found in the analysis of the clinical examination of visual functions by the radiation oncologist. However, considering VEP, the impairment was statistically significant for both fibers explored at 30'angle (p:0.007) and 60'angle (p <0.001). In patients with toxicity, the distance of the target volume from the optical pathways was more important with a p-value for 30’VEP at 0,035 and for 60’VEP at 0,039. Conclusions: These results confirm uncertainties concerning elative biological effectiveness of proton therapy, linear energy transfer appears to be more inhomogeneous especially in areas close to the target volumes. The follow-up of patients after proton therapy is not an easy process to set up but it is necessary to improve our knowledges about the biological effects of proton therapy in real life. Our study which will continue during the coming years, suggests that follow-up with in-depth examinations such as VEP as a biomarker could improve the detection of early abnormalities.